2011
DOI: 10.1523/jneurosci.0710-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mithramycin Is a Gene-Selective Sp1 Inhibitor That Identifies a Biological Intersection between Cancer and Neurodegeneration

Abstract: Oncogenic transformation of postmitotic neurons triggers cell death, but the identity of genes critical for degeneration remain unclear. The antitumor antibiotic mithramycin prolongs survival of mouse models of Huntington’s disease in vivo and inhibits oxidative stress-induced death in cortical neurons in vitro. We had correlated protection by mithramycin with its ability to bind to GC-rich DNA and globally displace Sp1 family transcription factors. To understand how antitumor drugs prevent neurodegeneration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 69 publications
6
112
1
Order By: Relevance
“…Mithramycin A, recognized as an inhibitor of Sp1 oligonucleotide binding (37,38), also inhibited the increases in Wnt9A expression that followed carrageenan and ARSB silencing in the NCM460 cells (Fig. 7C).…”
Section: Expression Of Wnt9a Is Increased After Carrageenan or Arsb Smentioning
confidence: 84%
See 1 more Smart Citation
“…Mithramycin A, recognized as an inhibitor of Sp1 oligonucleotide binding (37,38), also inhibited the increases in Wnt9A expression that followed carrageenan and ARSB silencing in the NCM460 cells (Fig. 7C).…”
Section: Expression Of Wnt9a Is Increased After Carrageenan or Arsb Smentioning
confidence: 84%
“…Inhibition of Sp1 Oligonucleotide Binding by Mithramycin AMithramycin A, a known inhibitor of Sp1 oligonucleotide binding (37,38), was purchased (Sigma). Control, carrageenan-exposed, and ARSB-silenced NCM460 cells were treated with mithramycin A (250 nM for 24 h), and the impact on Wnt9A expression was determined by QRT-PCR, as above.…”
Section: Arsb Galectin-3 and Sp1mentioning
confidence: 99%
“…Pretreatment of WT BMDM with mithramycin A, a specific Sp1 inhibitor, 40,41 prevented BCM-induced expression of caveolin-1 mRNA and protein (Figures 5a and b), as well as BCM reduced Mϕ surface expression of TLR4, a reflection of TLR4 internalization ( Figure 5c). …”
Section: Figure 1 Continuedmentioning
confidence: 95%
“…Based on the previous observation that MA could effectively prevent the binding of SP1 to the CAR promoter (Chung et al 2011), we blocked SP1 using MA and then observed for TNFa core promoter activity in the ERa-transfected cells. Ectopic expression of ERa enhanced TNFa promoter activity, and this promoter activity was abolished by the SP1 inhibitor (Sleiman et al 2011). These observations suggest that ERa is able to bind to TNFa in the presence of estrogen stimulation and enhance its transcription; however, deletion of the SP1 site in the TNFa promoter region blocked its transcription.…”
Section: Figurementioning
confidence: 98%